ANALISIS PENGGUNAAN ZAT PEWARNA SINTETIS, PENGAWET,PENYEDAP RASA PADA BEBERAPABUMBU GILINGYANG DIPASARKAN DI PUSAT PASAR TRADISIONAL KOTA MEDAN TAHUN 2016 - Rut Seylina Sinambela; Evawany Y Aritonang; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Blended cooking spices is result of milling aromatic plants porridge which are consumed in form of mixed causine. It made is done by home industry, so the rule of use kind and content of food additives substance is not permanent yet. In general, it can last a maximum of four days until they rot. The purpose of this study was to determine the presence of food additives include synthetic coloring substance, preservatives, flavoring in varios blended cooking spices. This research was a descriptive survey using chromatography paper method to know whether there is or no the usage of synthetic coloring substance, the gravimetric method to know the dose of synthetic coloring substance, reaction of curcumin method to know whether there is or no the useage of borax, esterification methods to know whether there is or no the useage of sodium benzoate, the titration method to know the dose of sodium benzoate and non-aqueous titration method to know the presence and dose of useage of flavoring such as MSG (Monosodium Glutamate). The samples was taken by purposive that were 5 traditional market seller in Pusat pasar Traditional Medan which consist of 5 each.                Based on the research showed that from those 25 item samples consisting of 5 kinds of blended cooking spices found 10 sample positif used sodium benzoate derived from two merchants, namely merchant II and V but only two samples that exceed specified dose that ground grilled pepper at 812 mg/kg and garlic milled at 828 mg/kg are derived from the merchant V. The overall of sample was not found to contain synthetic coloring substance, borax, MSG (Monosodium Glutamate). Therefore, the grilled chili and garlic milled which was coming from merchants V in Pusat Pasar are unsafe to consumed because it was not based on the health regulation by Minister of Health of RI No.033 in 2012. It is recommended to the Drug and Food Controlling Office (BPOM) Medan to do control and periodic evaluation of food products, especially product of home industry in traditional markets. People are suggested to avoid using blended cooking spices sold in the tradisional market. Key word:  blended cooking spices, synthetic coloring substance, preservatives,        flavoring